ECE2 regulates neurogenesis and neuronal migration during human cortical development. (24th March 2020) - Buchsbaum, Isabel Y; Kielkowski, Pavel; Giorgio, Grazia; O'Neill, Adam C; Di Giaimo, Rossella; Kyrousi, Christina; Khattak, Shahryar; Sieber, Stephan A; Robertson, Stephen P; Cappello, Silvia
Abstract: During embryonic development, excitatory projection neurons migrate in the cerebral cortex giving rise to organised layers. Periventricular heterotopia (PH) is a group of aetiologically heterogeneous disorders in which a subpopulation of newborn projection neurons fails to initiate their radial migration to the cortex, ultimately resulting in bands or nodules of grey matter lining the lateral ventricles. Although a number of genes have been implicated in its cause, currently they only satisfactorily explain the pathogenesis of the condition for 50% of patients. Novel gene discovery is complicated by the extreme genetic heterogeneity recently described to underlie its cause. Here, we study the neurodevelopmental role of endothelin‐converting enzyme‐2 ( ECE2 ) for which two biallelic variants have been identified in two separate patients with PH. Our results show that manipulation of ECE2 levels in human cerebral organoids and in the developing mouse cortex leads to ectopic localisation of neural progenitors and neurons. We uncover the role of ECE2 in neurogenesis, and mechanistically, we identify its involvement in the generation and secretion of extracellular matrix proteins in addition to cytoskeleton and adhesion. Synopsis: Using in vitro and in vivo models of cortical development, this study identifies biallelic missense mutations in endothelin‐converting‐enzyme‐2 as novel candidates causative for the neuronal migration disorder periventricular heterotopia. Modification of ECE2/Ece2 levels in cerebral organoids and in the developing mouse cortex cause ectopic positioning of neurons resembling that of patients with periventricular heterotopia. ECE2 promotes neuronal differentiation. ECE2's mechanism of action comprises a combination of cell‐intrinsic and non‐cell‐autonomous pathways, including a role in apical adhesion, cytoskeleton dynamics and extracellular matrix composition. Abstract : Using in vitro and in vivo models of cortical development, this study identifies biallelic missense mutations in endothelin‐converting‐enzyme‐2 as novel candidates causative for the neuronal migration disorder periventricular heterotopia.